2004
DOI: 10.1121/1.1736649
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting monaural and interaural spectral cues for human sound localization

Abstract: A human psychoacoustical experiment is described that investigates the role of the monaural and interaural spectral cues in human sound localization. In particular, it focuses on the relative contribution of the monaural versus the interaural spectral cues towards resolving directions within a cone of confusion (i.e., directions with similar interaural time and level difference cues) in the auditory localization process. Broadband stimuli were presented in virtual space from 76 roughly equidistant locations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…A number of studies demonstrated that people listening with just one ear can localize sound sources in the horizontal plane although such localization accuracy is much poorer than with two ears and all localization judgments are shifted toward the active ear (Belendiuk and Butler, 1975;Butler 1987;Butler and Flannery, 1980;Jin et al, 2004;Morimoto, 2001;Oldfield and Parker, 1984a;Van Wanrooij and Van Opstal, 2004). Such localization ability is proof that horizontal localization can, to some degree, be facilitated by monaural cues.…”
Section: Monaural Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies demonstrated that people listening with just one ear can localize sound sources in the horizontal plane although such localization accuracy is much poorer than with two ears and all localization judgments are shifted toward the active ear (Belendiuk and Butler, 1975;Butler 1987;Butler and Flannery, 1980;Jin et al, 2004;Morimoto, 2001;Oldfield and Parker, 1984a;Van Wanrooij and Van Opstal, 2004). Such localization ability is proof that horizontal localization can, to some degree, be facilitated by monaural cues.…”
Section: Monaural Cuesmentioning
confidence: 99%
“…The relative importance of the interaural spectral cues to the localization of sound sources at different elevations is hard to generalize since it varies with the lateral position of the sound source (e.g., Jin et al, 2004). Oldfield and Parker (1986) demonstrated that monaural localization in the vertical plane, which does not take advantage of the interaural spectral cues, is 15 relatively good but somewhat less accurate than binaural localization.…”
Section: Monaural Cuesmentioning
confidence: 99%
“…These effects and reflections produce peaks and troughs in the sound spectrum that are unique for each sound source location in space relative to the position of the listener (Bloom, 1977;Butler & Belendiuk, 1977;Watkins, 1978). Monaural cues and the related Interaural Spectrum Difference (ISD) also help binaural horizontal localization (Jin et al, 2004;Van Wanrooij & Van Opstal, 2004), but they are most critical for vertical localization and front-back differentiation. The spectral cues that are the most important for accurate front-back and up-down differentiation are located in the 4-16 kHz frequency range (e.g., Langendijk & Bronkhorst, 2002).…”
Section: Basis Of Auditory Localizationmentioning
confidence: 99%
“…Previous studies on elevation illusions and elevation localisation used different sound sources, such as noises of different bandwidths, random signals, etc. [5,11,15,16,25], to demonstrate the correlation between the perceived elevation and the frequency centroid of a sound [22,31], i.e. that the sounds with higher pitch appeared to the listener as if originating from higher elevation.…”
Section: Introductionmentioning
confidence: 99%